Anatomical and phytochemical studies and ethnomedicinal uses of Colchicum autumnale L. - Boboev, Sarvar; Makhkamov, Trobjon; Bussmann, Rainer W; Zafar, Muhammad; Yuldashev, Akramjon (Ethnobotany Research and Applications, 2023)
Background: In the world, great importance is attached to the intensification of plants. To date, most medicinal plants are only partially used. In case of Colchicum autumnale L. currently mainly the corms are used for the extraction of alkaloids. The purpose of this study was to investigate the intensification of the use of this perspective plant reported from the study area. This article examines the anatomy and phytochemistry of leaf and corm of C. autumnale, which is grown as a medicinal crop in Uzbekistan. Methods: The leaves were fixed in 70% ethanol according to the generally accepted method; transverse and paradermal sections were examined on the fixed material. When studying the anatomical features of the leaf, preparations was formed by manually cutting a transverse section of the leaf were observed by a MOTIC V1 microscope. The slides were stained with glycerin jelly having safranin. Cells and tissues were measured using a micrometer MOB-15. To determine the amount of alkaloids contained in the leaves and in corms, a chemical analysis was carried out in the laboratory of alkaloids of the Institute of Chemistry of Plant Substances. Results: On the transverse section of the stomata of the leaves of Colchicum autumnale anomocytic type, 2-3 rows of parenchyma and palisade cells, the characteristic size of the stomata. The root structure of C. autumnale consists of 4-5 rows of corolla, 4 protoxylems and 1 metaxylem, and the presence of rhomboid calcium oxalate crystals in its parenchyma is a characteristic feature of the species. As a result of studying the chemical composition of the plant in the conditions of the Tashkent region, it was observed that the amount of alkaloids in the aerial part of the colchicum, in the leaves was 0.4% and in the corm 0.14%. Conclusion: The current work sought to resolve taxonomic issues involving species that share the majority of their physical characteristics and to clarify relationships between important taxa by utilizing leaf epidermal characteristics. As a result of chemical analysis, it was revealed that the amount of alkaloids in the leaves of Colchicum autumnale, introduced in the conditions of the Tashkent region (Uzbekistan), is higher than in natural regions. This proves that in the conditions of Uzbekistan it is possible to grow Colchicum and obtain high-quality raw materials. Key words: autumn crocus, meadow saffron, anatomy, phytochemistry, ethnomedicine.